Expanded Phenotype of the Cln6nclf Mouse Model - Victoria Chaoul; Sara Saab; Omar Shmoury; Ramy Alam; Lynn Al Aridi; Nadine J. Makhoul; Jihane Soueid; Rose-Mary Boustany (Cells)
Neuronal ceroid lipofuscinoses (NCLs) are a group of autosomal recessive neurogenetic disorders caused by mutations in 14 different genes. CLN6 disease manifests as variant late-infantile NCL (vLINCL) or as an adult variant. In childhood, symptoms include speech delay, vision loss, cognitive and motor decline, seizures, and early death. An in-depth characterization of a naturally occurring Cln6 mutant mouse (Cln6nclf) is presented, with implications for translational research. The expanded phenotype provides data showing early death, vision loss, and motor deficits in male and female Cln6nclf mice. Diminished visual acuity in Cln6nclf mice was noted at 28 weeks of age, but the pathological loss of retinal layers began as early as 2 weeks or postnatal day 14 (P14). Apoptosis was confirmed by TUNEL staining in the Cln6nclf mouse brain at P8 and in the retina at P12. A peak in glial fibrillary acidic protein (GFAP) expression was established as a normal developmental phenomenon in the wild-type and Cln6nclf mouse brain cerebellum and the CA2–CA3 regions of the hippocampus at P8. In Cln6nclf mice, GFAP levels were elevated at P12 in the cerebellum and hippocampus. In the retina, a developmental peak in gliosis was absent, with increased astrogliosis noted at P6 and P8 in female and male Cln6nclf mice, respectively. This highlights the lack of a sex-dependent response in wild-type mice. These novel data position the Cln6nclf mouse model as a useful tool for screening potential therapeutics for human CLN6 disease.